Charge Density and Band Offsets at Heterovalent Semiconductor Interfaces. Issue 1 (1st December 2017) - Tung, Raymond T.; Kronik, Leeor
Abstract : The well‐known insensitivity of the band offset (BO) of isovalent heterojunctions with the zincblende structure to the orientation, abruptness, and atomic structure of the interface was recently shown to be attributable to a localness in the dependence of charge density on the atomic structure. In contrast, a sharp dependence of the BO on interface specifics has been observed at heterovalent heterojunctions. Here, detailed analyses of the relationship between the BO, interface structure, and charge distribution have been carried out for many lattice‐matched heterovalent interfaces between zincblende and diamond structure semiconductors. From thermodynamic considerations, three types of neutral interfaces were investigated, each with equal densities of donor‐ and acceptor‐like heterovalent bonds, constructible in all orientations. Distinctively different, yet approximately orientation‐independent, valence BOs were found. The equilibrium charge density of the heterovalent interface could be recreated with the charge densities of bulk semiconductors and oligo‐cells. Because charge transfer between heterovalent bonds is identifiable with that for dopants in semiconductor and its effect accountable by linear response, a combination of neutral polyhedra theory, previously developed for isovalent heterojunctions, and dielectric screening theory was found to explain BO trends throughout, allowing a strategy that facilitates adjustment in the BO of all isovalent heterojunctions. Abstract : Band offset trends at heterovalent heterojunctions are explained in terms of the underlying charge density. Potential energy profiles for the GaAs/ZnSe heterojunction demonstrate that the band offset depends strongly on the interface structure (compare cation‐centered (CC) and anion‐centered (AC) junctions), but is nearly independent of interface orientation. We explain this by combining neutral polyhedra theory and dielectric screening theory.